The biomechanical effects of insoles with different cushioning on the knee joints of people with different body mass index grades - Jia, Rui; Wang, Fei; Jiang, Jiang; Zhang, Hongtao; Li, Jianyi (Frontiers in Bioengineering and Biotechnology, 2023)
Background: Enhancing knee protection for individuals who are overweight and obese is crucial.Cushioning insoles may improve knee biomechanics and play a significant protective role.However, the impact of insoles with varying cushioning properties on knee joints in individuals with different body mass index (BMI) categories remains unknown. Our aim was to investigate the biomechanical effects of insoles with different cushioning properties on knee joints across different BMI grades. Methods: Gravity-driven impact tests were used to characterize the cushioning properties of three types of Artificial Cartilage Foam (ACF18, 28, and 38) and ethylene-vinyl acetate (EVA) insoles. Knee joint sagittal, coronal, and vertical axis angles and moments were collected from healthy-weight (BMI 18.5-23.9 kg/m 2 , n=15), overweight (BMI 24.0-27.9 kg/m 2 , n=16), and obese (BMI ≥28.0 kg/m 2 , n=15) individuals randomly assigned four different insoles during a drop jump. The Kruskal-Wallis test and mixed model repeated measures analysis of variance were used to compare differences among cushioning and biomechanical data across various insoles, respectively. Results: ACF showed higher cushioning than EVA, and ACF38 was the highest among the three types of ACF (all P<0.001). During the drop jump, the knee flexion angles and moments of the ACF insoles were lower than those of the EVA insoles, the knee adduction angles of the ACF18 and ACF28 insoles were lower than those of the EVA insoles, and ACF18 insoles increased the first cushion time (all P<0.05) for all participants in whom biomechanical variables demonstrated no interactions between insoles and BMI. Regarding the BMI-dependent biomechanical variables, compared with the EVA insoles, ACF28 insoles decreased the knee flexion angle and ACF38 insoles decreased the knee adduction and rotation moment in the healthy-weight group; ACF18 insoles decreased the knee flexion angle and ACF38 insoles decreased the knee moment in the overweight group; ACF28 insoles decreased the knee flexion and adduction moment, and ACF38 insoles decreased the knee flexion angle and rotation moment in the obese group (all P<0.05). Conclusions: Insoles with higher cushioning properties could improve knee biomechanics and provide better knee joint protection in people across different BMI ranges.